The impact of climacteric symptoms on functioning and quality of life among women in perimenopausal stage - Skrzypulec, Violetta; Naworska, Beata; Drosdzol, Agnieszka (Menopause Review/Przegląd Menopauzalny, 2007)
Objectives and study design: The aim of this study is to evaluate the impact of climacteric symptoms on functioning and quality of life among perimenopausal women. Materials and method: A group of 1049 women in perimenopausal stage at the age of 45-65 living in Silesia and Warmia Regions were screened for inclusion in the study. A specific questionnaire was used as a research tool in this study. It included a general/sociodemographic part, medical history, psychological part and Kupperman Index. In statistical analysis CHI2, U Mann-Whitney, analysis of variance and Spearman’s rank correlation models were used. Results: There were no significant differences between the two female groups (GS and GW) on the mean age (respectively: GS 51.31±5.26 and GW 51.62±5.81; p>0.09). The mean age of menopause was 49.23±4.37 in the present study. The study revealed generally low Kupperman Index scores both in GS and GW (mean 16.34 points) which suggests a very low intensification of the climacteric syndrome. The age of GS and GW respondents (p<0.01), living alone (p<0.036), bad financial situation (p<0.001) and not using hormonal therapy correlated with higher IK scores. Hot flushes and sweating were classified as the most troublesome. The level of hot flushes significantly correlated with changes in occupational functioning among GS (p<0.01) and sweating with both family and occupational one among GW (p<0.01). Conclusions: Climacteric symptoms are intensified by age, bad financial situation, living alone and not using hormonal therapy, which has a negative influence on family and occupational functioning.